Stress responses of the fish Nile tilapia subjected to electroshock and social stressors - Barreto, R.E. [UNESP]; Volpato, Gilson Luiz [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2006)
Plasma cortisol and glucose levels were measured in 36 adult Nile tilapia males, Oreochromis niloticus (standard length, mean ± SD, 14.38 ± 1.31 cm), subjected to electroshock and social stressors. Pre-stressor levels were determined 5 days after the adjustment of the fish to the experimental aquaria (1 fish/aquarium). Five days later, the effects of stressors on both cortisol and glucose levels were assessed. The following stressors were imposed for 60 min: pairing with a larger resident animal (social stressor), or a gentle electroshock (AC, 20 V, 15 mA, 100 Hz for 1 min every 4 min). Each stressor was tested in two independent groups, one in which stress was quantified immediately after the end of the 60-min stressor imposition (T60) and the other in which stress was quantified 30 min later (T90). Pre-stressor values for cortisol and glucose were not statistically different between groups. Plasma cortisol levels increased significantly and were of similar magnitude for both electroshock and the social stressor (mean ± SD for basal and final samples were: electroshock T60 = 65.47 ± 15.3, 177.0 ± 30.3; T90 = 54.8 ± 16.0, 196.2 ± 57.8; social stress T60 = 47.1 ± 9.0, 187.6 ± 61.7; T90 = 41.6 ± 8.1, 112.3 ± 26.8, respectively). Plasma glucose levels increased significantly for electroshock at both time points (T60 and T90), but only at T90 for the social stressor. Initial and final mean (± SD) values are: electroshock T60 = 52.5 ± 9.2, 115.0 ± 15.7; T90 = 35.5 ± 1.1, 146.3 ± 13.3; social stress T60 = 54.8 ± 8.8, 84.4 ± 15.0; T90 = 34.5 ± 5.6, 116.3 ± 13.6, respectively. Therefore, electroshock induced an increase in glucose more rapidly than did the social stressor. Furthermore, a significant positive correlation between cortisol and glucose was detected only at T90 for the social stressor. These results indicate that a fish species responds differently to different stressors, thus suggesting specificity of fish stress response to a stressor.
Keywords: Stress; Aggression; Agonistic behavior; Fighting; Social stress; Electroshock